Analysis of Microservice Evolution Using Cohesion Metrics - Moreira, Mateus Gabi; França, Breno Bernard Nicolau de (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2022: Anais do XVI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2022)
The adoption of Microservices Architecture (MSA) has increased in recent years due to several claimed benefits, such as reducing deployment complexity, supporting technology diversity, and better scalability. However, MSA is not free from maintainability issues, especially the lack of cohesion, in which microservices possibly concentrate or miss responsibilities. Also, the lack of empirically-validated cohesion metrics for MSA makes the quantitative assessment even more challenging. In this paper, we empirically explore the practical applicability of service-level cohesion metrics in an open-source MSA application context. The qualitative results show the possibility of assessing MSA cohesion using these service-level metrics, the feasibility of tracking software evolution, and an indication of possible technical debts along the way.